Trends and Patterns in Euro‐Marriages in the Netherlands. Issue 2 (29th January 2013) - van, Leo J. G.; Heering, Liesbeth; de, Helga A. G.; Medrano, Juan Díez
ABSTRACT Although the European Union is usually viewed as a project aimed at creating a single commodity market, one of its primary purposes was more generally to remove social and cultural boundaries between the European nation‐states. Intermarriage is a classical indicator of the formation of social ties and communities. One could claim that the creation of a real social, political, cultural, and supranational European space is only complete if people are also willing to accept each other as their spouses. As part of Europe's social integration, Euro‐marriage can be regarded as the litmus test of European integration, and the Netherlands with his status as a founding member should have enjoyed the benefits of one single European marriage market longer than more recent members. Despite this obvious role of intermarriage as a key indicator of European integration, little is known about marriages between Europeans ('Euro‐marriages') in the Netherlands. This paper tries to fill this gap by describing the patterns of Euro‐marriages in the Netherlands, on the basis of register data on bi‐national newlyweds and household structure in the Netherlands since 1995. One of the key findings is that Euro‐marriages have not become more popular since 1995 and that this is only to some extent compensated by increased cohabitation. Copyright © 2013 John Wiley & Sons, Ltd.